Risk Analysis of Dual Fuel Tug Ship Design in Maritime Technology Development Innovation Program – BRIN - Kartikasari, Dewi; Muhajirin, Muhajirin; Waluyo, Waluyo; Sadiah, Siti; P, Dany H (International Journal of Offshore and Coastal Engineering (IJOCE), 2023)
The problem that often occurs in the ship design process is the deviations in time and quality of results. IMO [1] regulations provide a methodology that ship design should be carried out with a risk-based probabilistic approach. This paper aims to become a source of reference information for ship design innovations in supporting efforts to increase performance optimization and efficiency. In the dual fuel tugboat design carried out in the BRIN Maritime Technology Development Innovation Program with funding from the government, the risk analysis begins with identifying and collecting data on control systems and internal controls based on existing risks, data collection on regulations, operational procedures, ship design business processes, and measuring the probability of risk occurrence. Furthermore, the level of risk is ensured by looking at the risk analysis matrix and making a risk map. The results of the analysis show that there are 3 risk events with a high-risk status that can lead to reduced quality and delays in the completion of the tugboat design, which is a skill base, experience, and the ship model test schedule.